Cost-efficient multi-energy management with flexible complementarity strategy for energy internet - Si, Fangyuan; Wang, Jinkuan; Han, Yinghua; Zhao, Qiang; Han, Peng; Li, Yan (Applied energy, 2018)
•A multi-energy management method with energy complementarity prosumers was proposed.•A multi-objective optimisation framework was developed to reduce total energy cost.•The economic impact of the energy complementarity strategy was investigated.•The new method could promote the sustainable development of the urban energy system. The increasing complexities of energy internet integrated with distributed renewable energy resources and multiple energy infrastructures require more effective multi-energy management method. The prosumers with multiparty interaction represent major potential contributors for comprehensively improving the energy efficiency and socioeconomic benefits. In this paper, a novel multi-energy management strategy based on the complementarity of multi-energy demand was proposed to explore optimal energy scheduling problems of prosumers. The residential prosumer with a multi-energy coupling matrix and the industrial prosumer with a resource-task network were formulated to optimise the local operations. Furthermore, a joint planning for the prosumers was developed to minimise the global operating costs, where the prosumers’ interests in terms of the energy exchange process were formulated as a multi-objective optimisation problem based on the Pareto efficiency theory. In addition, an optimisation method that integrates the epsilon-constraint algorithm and the extreme points of the feasible solution space was proposed to obtain better and more diverse solutions. The proposed methodology was applied to an urban multi-energy system. Simulation results demonstrated that the proposed multi-energy management method could effectively solve the optimal energy scheduling problems. At the compromise solution point, cost reductions of 7% and 10% can be obtained by the two prosumers on a summer day, with cost reductions of 9% and 11% obtained on a winter day. The use of multi-energy management method could establish a win-win relationship for prosumers and generate substantial benefits for the whole system.